Microbiome of traditional Chinese soy sauce fermentation brine / Joanita binti Sulaiman - Sulaiman, Joanita (2014)
The traditional Chinese soya sauce quality is determined by the corresponding metabolic behaviour of microbial population in the fermentation tank. In this study, the microbiome changes and functional capabilities throughout the traditional Chinese soya sauce brine fermentation process in a period of six months were investigated. Samples were obtained from soya sauce fermentation tank recurrently during the six months of the fermentation process. The metagenomes were analyzed using whole-genome shotgun (WGS) sequencing via next generation sequencing (NGS) on MiSeq (Illumina) platform. Alignment of the sequence reads with 16S rRNA and 18S rRNA genes revealed that soya sauce microbiome was predominated by members of the bacterial genus Weissella in the early stages and later succeeded by members of the fungal genus Candida at the end of the fermentation process. Upon analysis of the metabolic reconstructions displayed genetic potential with the majority of the genes were responsible for carbohydrate and energy metabolism besides the production of acid amino metabolism. Kyoto Encyclopedia of Genes and Genomes (KEGG) classification scheme using MetaGenome Analyzer (MEGAN) demonstrated a typical profile of heterotrophic fermentation of proteins and carbohydrates in which collaborated with the biochemical adjustments. This study provides new findings and insight of temporal changes in microbial successions over the six months of soya sauce brine fermentation and the biological processes within.